Twice upon a time : selected stories, 1898-1939 - Montgomery, L. M. (Lucy Maud), 1874-1942 (Montgomery, L. M. (Lucy Maud), 1874-1942. L.M. Montgomery library., 2022)
"This collection of short stories by L.M. Montgomery reveals the early workings of parts of Anne of Green Gables, its sequels, and her other ever-popular novels."--